The BODO (BORO) problems in Assam: Searching remedies - Shashi Bhushan Kumar (2016)
The North-Eastern region of India, has long remained one of the most volatile and sensitive regions in the country because of the problems of the border management, insurgency, ethnic conflict, pressure of immigration, underdevelopment, etc. Facing indignation on various counts, prominently immigration of Muslim settlers from Bangladesh, the Bodos started an armed struggle, for a separate state in the mid-1980s, which led to ethnic cleansing of the non-Bodos along the north bank of the Brahmaputra. In 1993, the Bodoland Autonomous Council (BAC) Accord was signed but Bodoland movement has not been contained by signing of the Accord. In February 2003, the Bodoland Territorial Council (BTC) came into existence. But the violence, which erupted in 2012 and 2014 between Bodos and Muslims indicates that Bodo problem still persists in this region and new Accord did not satisfy non-Bodos in the BTC. The present article is an attempt to understand the ethnic autonomy movements in the North-East region of India with special reference to the Bodo problem. - Reproduced.
Keywords: Indigenous populations - India - Assam; Indigenous populations